Improving Accounting Understanding Through Mathematical Logical Intelligence and Emotional Intelligence Through Learning Interest Student At Mahkota Tricom Superior University - Debora Tambunan; Fiqrida Amalia; Yesika Yanuarisa; Susan Grace Veranita Nainggolan; Zakia Fadila (Jurnal Mantik, 2022)
The purpose of this study is to determine the effect of logical-mathematical intelligence and emotional intelligence on accounting understanding through an interest in learning at Mahkota Tricom Unggul University. This type of research is associative research. The population and sample are active students at Mahkota Tricom Unggul University, totaling 195 active students for the 2020-2021 academic year. Then the sampling technique uses total sampling. Data analysis uses path analysis which is to determine the direct or indirect effect. The independent variable on the dependent variable and the role of the mediating variable. The results showed that 1. Logical-mathematical intelligence had a significant effect on students' interest in learning. 2. Emotional intelligence has a significant effect on student interest in learning. 3. Logical-mathematical intelligence has a significant effect on students' accounting understanding. 4. Emotional intelligence has a significant effect on students' accounting understanding. 5. Interest in learning has a significant effect on students' understanding of accounting. 6. Logical-mathematical intelligence has a significant effect on students' accounting understanding through an interest in learning. 7. Emotional intelligence has a significant influence on accounting understanding through an interest in learning